Measurement of Typhi Vi antibodies can be used to assess adaptive immunity in patients with immunodeficiency. (1st April 2018) - Evans, C; Bateman, E; Steven, R; Ponsford, M; Cullinane, A; Shenton, C; Duthie, G; Conlon, C; Jolles, S; Huissoon, A P; Longhurst, H J; Rahman, T; et al.
Summary: Vaccine-specific antibody responses are essential in the diagnosis of antibody deficiencies. Responses to Pneumovax II are used to assess the response to polysaccharide antigens, but interpretation may be complicated. Typhim Vi ®, a polysaccharide vaccine for Salmonella typhoid fever, may be an additional option for assessing humoral responses in patients suspected of having an immunodeficiency. Here we report a UK multi-centre study describing the analytical and clinical performance of a Typhi Vi immunoglobulin (Ig)G enzyme-linked immunosorbent assay (ELISA) calibrated to an affinity-purified Typhi Vi IgG preparation. Intra- and interassay imprecision was low and the assay was linear, between 7·4 and 574 U/ml (slope = 0·99–1·00; R 2  > 0·99); 71% of blood donors had undetectable Typhi Vi IgG antibody concentrations. Of those with antibody concentrations  > 7·4 U/ml, the concentration range was 7·7–167 U/ml. In antibody-deficient patients receiving antibody replacement therapy the median Typhi Vi IgG antibody concentrations were  < 25 U/ml. In vaccinated normal healthy volunteers, the median concentration post-vaccination was 107 U/ml (range 31–542 U/ml). Eight of eight patients (100%) had post-vaccination concentration increases of at least threefold and six of eight (75%) of at least 10-fold. In an antibody-deficient population ( n  = 23), only 30% had post-vaccination concentration increases of at least threefold and 10% of at least 10-fold. The antibody responses to Pneumovax II and Typhim Vi ® correlated. We conclude that IgG responses to Typhim Vi ® vaccination can be measured using the VaccZyme Salmonella typhi Vi IgG ELISA, and that measurement of these antibodies maybe a useful additional test to accompany Pneumovax II responses for the assessment of antibody deficiencies. Graphical Abstract: